Failure to eliminate the carrier state of Anaplasma marginale by using long-acting injectable oxytetracycline - Gnad, D.; Marston, T.; Llewellyn, Donald A.; Palmer, G.; Hollis, Larry C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-four Anaplasma marginale seropositive cows from a herd of 236 were allocated to treatments: 5 animals served as untreated controls, and 29 animals were treated with three injections of long-acting oxytetracycline at three-day intervals. Fourteen days after initiation of treatment, 100% of control cows and 89% of treated cows were found to have Anaplasma marginale present. Seventyfour days after initiation of treatment, 100% of control cows and 86% of treated cows were found to have Anaplasma marginale present. Use of injectable long-acting oxytetracycline was not effective in eliminating the carrier state of Anaplasma marginale from infected animals.
Keywords: Beef; Anaplasma marginale; Oxytetracycline